Sistem Informasi Administrasi Pelayanan Pendaftaran Zakat dan Wakaf di Kantor Kementerian Agama Sampit Kabupaten Kotawaringin Timur - Wulandari, Antika; Minarni, Minarni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
At the Office of the Ministry of Religion of East Kotawaringin Regency, the administrative process of registering zakat and waqf is still done manually, so that for less than optimal public services it takes a long time in the process, there are also obstacles to delays in making reports and the form of data storage which is still in the form of documents. archived and so that the data search process becomes slow. This will hamper the quality of service to the community. Therefore, it is necessary to design a system that can assist the process and provide information regarding the registration of zakat and waqf. By doing this research, it is hoped that the needs of the latest system and problems that often occur in data processing at the Sampit Religious Affairs Office, East Kotawaringin Regency by using the information system This website-based system can be handled properly, so that it can improve the performance of the parties involved in the data processing process in the form of the administration of zakat and waqf registration and can improve the service performance of the Sampit Religious Affairs Office, Kotim Regency